Environment, Ethics and Cultures
VI, 326 p.
Keywords: "This collection engages environmental, ethical and cultural values perspectives to show how Design and Technology (D&T) Education actively contributes to the significant educational goal of attaining sustainable global futures. An international collection of authors representing all levels of education articulate how D&T research, curriculum theory, policy, and classroom practices can synergise to contribute positively to the education of children for sustainable global futures. The book offers a spectrum of theorised curriculum positions, political and policy analysis, and case studies of successful school practice. A key word in the title is that of contribution which is construed in several senses: first, of D&T as a vehicle for understanding the range of political and social values that arise with such a major educational challenge; second, of D&T as an agent of critical and practical action for students as global citizens; third, by taking global and multiple perspectives (rather than, say, Western or mono-cultural positions); and, fourth, by demonstrating D&T’s capacities for working in holistic and integrative cross-curricular ways. The authors show how students can not only learn about their potential as humans-as-designers but can also develop designerly capacities that enable them to contribute meaningfully in practical ways to their communities and to wider society, that is, as global citizens who can apply design capability in ethical ways that are respectful of peoples, cultures and environments alike.".